Hippocampal morphometry in population-based incident Alzheimer's disease and vascular dementia: the HAAS. Issue 4 (8th September 2010) - Scher, Ann I; Xu, Yuan; Korf, Esther S C; Hartley, Stephen W; Witter, Menno P; Scheltens, Philip; White, Lon R; Thompson, Paul M; Toga, Arthur W; Valentino, Daniel J; Launer, Lenore J
Abstract : Background: Hippocampal changes may be a useful biomarker for Alzheimer's disease if they are specific to dementia sub-type. We compare hippocampal volume and shape in population-based incident cases of Alzheimer's disease and vascular dementia (VaD). Methods: Participants are Japanese-American men from the Honolulu Asia Aging Study. The following analysis is based on a sub-group of men with mild incident Alzheimer's disease ( n =24: age=82.5±4.6) or incident VaD ( n =14: age=80.5±4.5). To estimate hippocampal volume, one reader, blinded to dementia diagnosis, manually outlined the left and right formation of the hippocampus using published criteria. We used 3-D mapping methods developed at the Laboratory of Neuro Imaging (LONI) to compare regional variation in hippocampal width between dementia groups. Results: Hippocampal volume was about 5% smaller in the Alzheimer's disease group compared to the VaD group, but the difference was not significant. Hippocampal shape differed between the two case groups for the left ( p <0.04) but not right ( p <0.21) hippocampus. The specific region of the hippocampus that most consistently differed between the Alzheimer's disease and VaD cases was in the lateral portion of the left hippocampus. Our interpretation of this region is that it intersects the CA1 sub-region to a great extent but also includes the dentate gyrus (and hilar region) and subiculum. Conclusion: As indicated by shape analysis, there are some differences in atrophy localisation between the Alzheimer's disease and VaD cases, despite the finding that volume of the hippocampi did not differ. These findings suggest hippocampal atrophy in Alzheimer's disease may be more focal than in VaD.